2020
DOI: 10.1007/s40843-020-1298-x
|View full text |Cite
|
Sign up to set email alerts
|

Triethanolamine-mediated photodeposition formation of amorphous Ni-P alloy for improved H2-evolution activity of g-C3N4

Abstract: Developing efficient, stable, and low-cost novel electron-cocatalysts is crucial for photocatalytic hydrogen evolution reaction. Herein, amorphous NiP alloy particles were successfully modified onto g-C 3 N 4 to construct the Ni-P/ g-C 3 N 4 photocatalyst through a simple and green triethanolamine (TEOA)-mediated photodeposition method. It was found that the TEOA could serve as an excellent complexing agent to coordinate with Ni 2+ to form [Ni(TEOA)] 2+ complex, which can promote the rapid and effective deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…The conventional g‐C 3 N 4 was normally produced by a high‐temperature calcination process using various organic precursors (for instance, melamine, thiourea, dicyandiamide, et al). [ 26–28 ] Unfortunately, high‐temperature calcination usually causes severe aggregation and disordered combination of the fundamental s‐triazine units in the final g‐C 3 N 4 photocatalysts, leading to inefficient carrier transfer and limited active sites. [ 29,30 ] To further modify the photogenerared carrier transfer and decrease their combination rate, one of the effective routes is to improve the ordered combination of s‐triazine units and reduce the bulk defects of g‐C 3 N 4 photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional g‐C 3 N 4 was normally produced by a high‐temperature calcination process using various organic precursors (for instance, melamine, thiourea, dicyandiamide, et al). [ 26–28 ] Unfortunately, high‐temperature calcination usually causes severe aggregation and disordered combination of the fundamental s‐triazine units in the final g‐C 3 N 4 photocatalysts, leading to inefficient carrier transfer and limited active sites. [ 29,30 ] To further modify the photogenerared carrier transfer and decrease their combination rate, one of the effective routes is to improve the ordered combination of s‐triazine units and reduce the bulk defects of g‐C 3 N 4 photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…23,[25][26][27][28] The peaks at 852.4 and 869.8 eV are ascribed to Ni2p 3/2 and Ni2p 1/2 of Ni, 855.9 and 873.5 eV to Ni2p 3/2 and Ni2p 1/2 of Ni 2+ , and 861.2 and 879.6 eV to the shake-up satellite peaks of Ni 2+ . 17,[27][28][29][30] The peaks at 187.8 and 191.7 eV arise from B1s, the former is ascribed to B and the latter to B 3+ . 17,20 The peak at 129.3 eV is attributed to P with Co and Ni, whereas the peak at around 133.1 eV to the oxidized P. 19,27,29 These results indicated that Co, Ni, P, and B in the catalysts are both in atomic states and oxidation states.…”
Section: Resultsmentioning
confidence: 99%
“…17,[27][28][29][30] The peaks at 187.8 and 191.7 eV arise from B1s, the former is ascribed to B and the latter to B 3+ . 17,20 The peak at 129.3 eV is attributed to P with Co and Ni, whereas the peak at around 133.1 eV to the oxidized P. 19,27,29 These results indicated that Co, Ni, P, and B in the catalysts are both in atomic states and oxidation states. In addition, from the areas of the binding energy peaks, the amount of the oxidation states is more than that of the atomic states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…zinc ions, similar to that observed for other materials. [150][151][152][153][154][155][156][157] For example, g-C 3 N 4 -Zn 2+ @graphene oxide (SCN-Zn 2+ @GO) were prepared using chemical vapor deposition (CVD). 158 The bidentate ligand, SCN, may coordinate to the Zn 2+ ions to form cross-links with GO, and additionally changing the crystal structure of g-C 3 N 4 and introducing defect sites (Fig.…”
Section: Non-noble Metal Doped G-c 3 N 4 Nanocompositesmentioning
confidence: 99%